Engaging Parents in the Development and Testing of a Website to Support Social-Communication and Play Development for Preschoolers with Autism Spectrum Disorder. Issue 4 (December 2022) - Amsbary, Jessica; Lin, Mei-Ling; Savage, Melissa N.; Fanning, Leslie; Reszka, Stephanie; Watson, Linda R.; Boyd, Brian
Preschoolers with autism spectrum disorder (ASD) present with social-communication and play challenges and would benefit from interventions targeting these skills. One way to ensure this is by engaging parents in technological supports to learn about an intervention and increase home-school collaboration. Thus, a website could potentially address both needs. This study describes the initial developmental processes of one such website. Specifically, we describe how engaging parents as stakeholders in the website development enhanced its future usability and feasibility. Data were collected through focus groups, interviews, and surveys to obtain parent feedback about website usability and applicability and about the intervention. Survey data were descriptively analyzed. Focus group and interview data were analyzed using systematic qualitative analysis. Parents perceived the website to be useful in helping them target social-communication and play with their preschoolers with ASD and highlighted specific aspects of the website and intervention they perceived as effective. Child outcomes and parent fidelity to the intervention supported these perceived developmental gains. Findings suggest that engaging parents in developmental processes may help ensure usability and applicability of resources and interventions. Furthermore, findings support the use of technology to help parents learn to use an intervention with their preschoolers with ASD. Implications for research and practice are discussed.